Pengembangan Aplikasi Belajar Nahwu dan Shorof : Systematic Literature Review - Abied Dafiq, Aqwam Khanif (JATISI, 2024)
In the context of Arabic language learning, the development of Android-based learning applications becomes highly relevant, especially for Nahwu and Shorof materials that require in-depth understanding. This literature review aims to identify frequently used development methods for Android-based learning applications and to examine whether testing is conducted and the user segment of the application is specified. This study employs the Systematic Literature Review (SLR) method to evaluate 15 relevant journals from 2019 to 2024. The findings reveal that the most commonly employed method for developing Android-based learning applications is analysis, design, development, implementation and evaluation (ADDIE). Most developers conduct field testing on their products. The segment often targeted by developers is junior high school students.